(3GdeaGgje(B- (3GdCSS(B- (3GdhXGFas - (3fRGQ YHO GdeLjO(B, (3GdHQhGQjs; (3CMeO eMeO agej(B, (3GdHQRfLjs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2004)
(3GdJShjb GdfTCI hGdJWhQ hGdGgejI(B- (3eOGNd GdJShjb hadSaGJg(B- (3GdeSDhdjI GdELJeGYjI ddefXeI hGdJShjb GdeLJeYj(B- (3GdHjFI GdJShjbjI(B- (3JbSje hGSJgOGa GdShb(B- (3Sdhc GdeSJgdc(B- (3MeGjI GdeSJgdc hMbhbg(B- (3GSJQGJjLjI GdJShjb hGdJShjb GdESJQGJjLj(B- (3GdefJhL(B- (3GdSYQ hGdJSYjQ(B- (3ecGf GdJhRjY hGdJQhjLs
Keywords: (3GdJShjbs